Telaah Nilai Pepatah Minangkabau Dima Bumi Dipijak Disinan Langik Dijunjuang Dan Kontribusinya Dalam Konseling Budaya - Sabarrudin -; Silvianetri - (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Humans are social beings who need the help of other people who are around them, humans are also referred to as beings who are rational, socialized and able to determine their own destiny which results in humans having to be able to adapt to the local environment. Where the earth is stepped on, disinan langik dijunjuang is a form of expression of the value of the Minangkabau proverb which has value as a way of life for the Minangkabau people. Examining the value of this proverb is one of the aims of the researcher to examine the value contained and its contribution to cultural counseling. This study uses qualitative methods with a hermeneutic approach. The results of this study explain that: 1) the value contained in the saying where the earth is stepped on by the sky is held up is a form of self-adjustment or adaptation according to the local wisdom of the local community. 2) Collaboration between culture and counseling will facilitate the counseling process. 3) As an approach in preventing the occurrence of a problem related to adjustment.